Ruthenium-Catalyzed Oxidative C–H Bond Alkenylation of 2-Phenylimidazo[1,2-a]pyridine - Sawant, Devesh; Singh, Iqubal; Tulsyan, Gaurav; Abbagani, Kishor; Pardasani, Ram T. (Synlett, 2015)
Monoalkenylation of sp2 C–H bonds directed by the innate reactivity of imidazo[1,2-a]pyridine to afford 2-(2′-alkenylphenyl)imidazo[1,2-a]pyridine with high levels of diastereoselectivity is described. The methodology is employed to generate di-substituted alkenes by using a cationic ruthenium(II) catalyst in the presence of AgSbF6 and Cu(OAc)2·H2O under air.
Keywords: C–H activation; Diastereoselectivity; regioselectivity; ruthenium; alkenylation